Circadian Regulation of GluA2 mRNA Processing in the Rat Suprachiasmatic Nucleus and Other Brain Structures - Míková, Hana; Kuchtiak, Viktor; Svobodová, Irena; Spišská, Veronika; Pačesová, Dominika; Balík, Aleš; Bendová, Zdeňka (Molecular neurobiology, 2021)
The mammalian circadian system consists of a major circadian pacemaker located in the suprachiasmatic nucleus (SCN) of the hypothalamus and peripheral clocks in the body, including brain structures. The SCN depends on glutamatergic neurotransmission for transmitting signals from the retina, and it exhibits spontaneous 24-h rhythmicity in neural activity. The aim of this work was to evaluate the degree and circadian rhythmicity of AMPA receptor GluA2 subunit R/G editing and alternative flip/flop splicing in the SCN and other brain structures in Wistar rats. Our data show that the circadian rhythmicity in the SCN's GluA2 mRNA level was highest at dawn, while the circadian rhythm in R/G editing peaked at CT10 and the rhythmic flip varied with the acrophase at the late subjective night. The circadian rhythmicity was confirmed for R/G editing and splicing in the CA3 hippocampal area, and rhythmic variation of the flip isoform was also measured in the olfactory bulbs and cerebellum. The correlations between the R/G editing and alternative flip/flop splicing revealed a structure-dependent direction. In the hippocampus, the edited (G)-form level was positively correlated with the flip variant abundance, in accord with published data; by contrast, in the SCN, the flip variant was in associated more with the unedited (R) form. The edited (G) form and flop isoform also predominated in the retina and cerebellum.
Keywords: Circadian Rhythm; RNA Editing; messenger RNA; Rats; Suprachiasmatic nucleus; editace RNA; cirkadiánní rytmus; posttranskripční úpravy RNA; Rats, Wistar; mužské pohlaví; Exons; nucleus suprachiasmaticus; krysa rodu Rattus; Suprachiasmatic Nucleus; RNA Processing, Post-Transcriptional; Rat; Circadian clock; RNA, Messenger; zvířata; R/G editing; potkani Wistar; AMPA receptory; GluA2 subunit; Receptors, AMPA; exony; Male; Animals